Evaluating the potential of Protestant Christianity to stimulate democracy and good governance in sub-Saharan Africa through the valuing of the individual. Issue 2 (17th February 2019) - de Jager, Nicola; de Jager, Phillip
ABSTRACT: The global distribution of Christians is expected to change by 2050, with the largest proportion of Christians – more than a billion – residing in sub-Saharan Africa. Historical and empirical studies have argued for a positive relationship between the proportion of Christians – Protestants in particular – and the development of liberal democracy. A key explanation for this positive influence is cultural, namely the valuing of the individual. Could the growth in Christianity have the potential to influence democratic development and good governance in the sub-Saharan region? To test our hypotheses – (1) sub-Saharan states with proportionally larger Protestant populations are more likely to have higher levels of democracy and good governance, and (2) sub-Saharan states with growing Protestant populations are more likely to have increasing levels of democracy and good governance – we employ a longitudinal and cross-sectional study (a panel of data) using data from the World Christian Database, Polity IV and the International Country Risk Guide. Our data show that the population share of Protestants is positively related with both levels of and growth in democracy and good governance. With the spread of Protestantism we could expect the future improvement of democracy and governance in the region.